2006
DOI: 10.1029/2006gl026523
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory observation of oligomers in the aerosol from isoprene/NOx photooxidation

Abstract: [1] Compounds assigned to be oxidation products of isoprene (2-methyl-1,3-butadiene) have recently been observed in ambient aerosols, suggesting that isoprene might play an important role in secondary organic aerosol (SOA) formation due to its large global source strength. SOA yields from photooxidation of isoprene and NO x in a chamber agree fairly well with previous data. Matrix assisted laser desorption/ionization mass spectrometry showed the formation of high molecular weight compounds over the course of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
192
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(226 citation statements)
references
References 24 publications
30
192
2
2
Order By: Relevance
“…5). Dommen et al (32) observed lowervolatility isoprene SOA (which is consistent with the formation of oligomers) to form under dry rather than humid conditions, which is consistent with a mechanism that involves decomposition of the C 4 -hydroxynitrate-PAN into 2-MG and allows for subsequent esterification of 2-MG into the observed oligoesters. We do not, however, have conclusive chemical evidence to support the hypothesis that the C 4 -hydroxynitrate-PAN is the main precursor to the isoprene high-NO x SOA.…”
Section: Identification Of Mpan As Key Intermediate In Formation Of Ssupporting
confidence: 53%
“…5). Dommen et al (32) observed lowervolatility isoprene SOA (which is consistent with the formation of oligomers) to form under dry rather than humid conditions, which is consistent with a mechanism that involves decomposition of the C 4 -hydroxynitrate-PAN into 2-MG and allows for subsequent esterification of 2-MG into the observed oligoesters. We do not, however, have conclusive chemical evidence to support the hypothesis that the C 4 -hydroxynitrate-PAN is the main precursor to the isoprene high-NO x SOA.…”
Section: Identification Of Mpan As Key Intermediate In Formation Of Ssupporting
confidence: 53%
“…Isoprene is also known to have a small but significant yield of SOA mass formation. Depending on seed aerosol, initial precursor concentration and relative NO x levels, SOA yields in the range of 1-5 % were reported in the literature (Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Dommen et al, 2009). Including SOA from isoprene in calculations of the global SOA burden increases SOA by factors between 0.5 and 2 depending on scenarios used (Henze and Seinfeld, 2006).…”
Section: Resultsmentioning
confidence: 98%
“…Note that Virtanen et al (2010) found that particles formed in the plant chamber are in a glassy state, and we cannot rule out the possibility that the particles are initially in a liquid state, but become more glasslike and less volatile with the aging. Formation of lowvolatility components of SOA formed from photooxidation of α-pinene (Paulsen et al, 2006;Baltensperger et al, 2005), aromatic compounds (Kalberer et al, 2004;Baltensperger et al, 2005), and isoprene (Dommen et al, 2006) have also been observed even after the completion of gas-phase chemistry. Those components are usually as a result of formation of high molecular weight compounds from oligomerization or polymerization processes.…”
Section: Oh-and O 3 -Initiated Chemistrymentioning
confidence: 99%
“…Further oxidation of semi-volatile products in the gas and particle phase Chan et al, 2007) and secondary generation products (Ng et al, 2006) caused by OH and O 3 could also alter final SOA production. Moreover, organic products in the condensed phase may also undergo chemical reactions, affecting their physicochemical properties (Joutsensaari et al, 2004) and volatility (Paulsen et al, 2006;Dommen et al, 2006;Baltensperger et al, 2005;Kalberer et al, 2004). The volatility of 30 nm and 50 nm diameter SOA at temperature of 150 • C, formed in the OH-dominated and O 3 -initiated chemical systems, is displayed in Fig.…”
Section: Oh-and O 3 -Initiated Chemistrymentioning
confidence: 99%